MANAJEMEN PERIOPERATIF PADA HIPERTENSI - Wiryana, Made (journal of internal medicine; Vol. 9, No. 2 Mei 2008, 2012)
Hypertension is a leading cause of death and the most frequent preoperative abnormality in surgical patients, and become major risk factor for cardiac, cerebral, renal and vascular disease during intraoperative or post-operative periode. Agressive controlled hypertension will decrease complications due to the damage of end organs. Consequences by taking anti-hypertensive agents is the interaction with other medications that being used during surgery. Consideration must be taken especially due to the half life and adjustment dose of this medications. The National Committee 7 (JNC 7) on prevention, detection, evaluation and treatment of high blood pressure 2003, degree of hypertension can be classified into pre-hypertension (120-139/80-89), hypertension stage 1 (140-159/90-99 mmHg) and hypertension stage 2 (systolic pressure 160 mmHg or diastolic pressure 100 mmHg). According to the etiology, hypertension can be classified into primary hypertension (80-95%) and secondary hypertension (10- 15%) due to the causes. Usually hypertension always has association with abnormality of sympathetic activity, increasing the pheripheral vascular resistance (SVR) or increasing both of them. But the most common cause of hypertension is increasing the pheripheral vascular resistance. Management perioperative of hypertension includes evaluation and optimalised patients condition preoperative, management patients who under influenced of anesthetic agents and treatment post operative. Patient with hypertension incline to have instability haemodinamic and more sensitive to anesthesia and surgery procedures, so carefull must be taken at the beginning of anesthesia and surgery until post operatively, especially to control hemodynamic. The best monitoring for patient with hypertension is by using suitable anesthetic techniques, anesthetic agents and antihypertensive agents. Post operative hypertension can be happened due to several factors such as, inadequate antihypertensive agents, respiratory disturbance, pain, fluid overload, or distended of the bladder. Excellent perioperative management of hypertension patients before surgery will decrease morbidity and mortality rate
Keywords: perioperative management of hypertension, hypertensive disease